IMPLEMENTATION OF ARTICLE 86 OF LAW NUMBER 13 OF 2003 CONCERNING MANPOWER,OCCUPATIONAL SAFETY AND HEALTH TOWARD OPERATOR OF GAS STATION NUMBER 21.381.09 AT RAWA MAKMUR OF BENGKULU CITY - Sukma Jumiati; Candra Irawan; Ganefi Ganefi (Universitas Bengkulu, 2020)
Regarding labour protection, therefore the Law Number 13 of 2003 concerning Manpower,Article 86 Paragraph (1) Letter a and Paragraph (2) states that: